Access to functionalized luminescent Pt(ii) complexes by photoredox-catalyzed Minisci alkylation of 6-aryl-2, 2′-bipyridines. Issue 8 (7th January 2021) - Hagui, Wided; Cordier, Marie; Boixel, Julien; Soulé, Jean-François
Abstract : Photoredox catalysis is employed to design unprecedented C6′-functionalized 6-aryl-2, 2′-bipyridines to prepare (circularly polarized) luminescent cyclomatalated platinum(ii ) complexes. Abstract : Photoredox-mediated C–H bond alkylation of 6-aryl-2, 2′-bipyridines with N -(acyloxy)phthalimides is reported. The reaction exhibits excellent functional group tolerance, including chiral aliphatic groups. The influence of the incorporated C6′ -alkyl group on the photophysical properties of the corresponding (N^N^C) cyclometalated Pt(ii ) complexes is described, including chiroptical properties.